2007
DOI: 10.1089/aid.2006.0225
|View full text |Cite
|
Sign up to set email alerts
|

RANTES–28G Delays andDC-SIGN– 139C Enhances AIDS Progression in HIV Type 1-Infected Japanese Hemophiliacs

Abstract: The relationships between host immune factors and HIV-1 disease progression are still in dispute. Unlike CCR5Delta32, which has been found to delay disease progression of HIV-1, there still remain several factors whose effect on the clinical course is unconfirmed. To clarify the relationships, we selected seven single-nucleotide polymorphisms (SNPs) out of the previously reported factors, namely, RANTES promoter -28G/-403A, RANTES In1.1C, SDF-1 3'A, IL-4 promoter -589T, and DC-SIGN promoter -139C/-336C, and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 35 publications
5
17
1
Order By: Relevance
“…However, there is a clear trend towards slower rate of CD4 cell depletion in HIV-1-infected European Americans and Japanese [16]. However, reports have also shown protective effects of RANTES -28G on HIV disease progression in Thais [17] and delayed AIDS progression in HIV-1-infected Japanese haemophiliacs [18]. …”
Section: Introductionmentioning
confidence: 99%
“…However, there is a clear trend towards slower rate of CD4 cell depletion in HIV-1-infected European Americans and Japanese [16]. However, reports have also shown protective effects of RANTES -28G on HIV disease progression in Thais [17] and delayed AIDS progression in HIV-1-infected Japanese haemophiliacs [18]. …”
Section: Introductionmentioning
confidence: 99%
“…Different studies have shown that polymorphisms in DC-SIGN and L-SIGN genes can influence susceptibility and/or resistance to HIV-1 [11][12][13]18,19].…”
Section: Discussionmentioning
confidence: 99%
“…DC-SIGN and L-SIGN genes polymorphisms have been involved in protection and susceptibility to infections, including HIV-1, in different ethnic groups [6,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Although these results were not confirmed in subsequent studies in other ethnic groups in which the RANTES À28G frequency was lower than in the Japanese [Gonzalez et al, 2001;An et al, 2002;Zhao et al, 2004], McDermott et al reported that patients with RANTES À28G showed a clear trend towards slower rate of CD4 cell depletion in HIV-1 infected European Americans [McDermott et al, 2000]. Recent reports have shown the protective effect of RANTES À28G on HIV disease progression in Thais [Wichukchinda et al, 2006] while, delayed AIDS progression in HIV-1 infected Japanese hemophiliacs [Koizumi et al, 2007]. With respects to RANTES À403A variants, HIV-1 infected European American with RANTES À403A were initially reported to progress more slowly to AIDS [McDermott et al, 2000].…”
Section: Introductionmentioning
confidence: 88%
“…Recent studies of other populations reported that À403G allele may be associated with increased susceptibility to HIV infection [Zhao et al, 2004] whereas, no such association of RANTES À403 A/G and À28C/G polymorphism could be established in HIV-1 infected Ugandans [Cooke et al, 2006], North Indians [Suresh et al, 2006], and Spanish populations [Vidal et al, 2006]. In vitro functional data, acquired using luciferase reporter assays in transfected jurkat cells, demonstrated that the RANTES In1.1C allele was associated with reduced RANTES expression thus contributing to the rapid progression of AIDS in European-Americans and African-Americans [An et al, 2002], however, the SNP was not found to influence disease progression in Japanese Hemophiliacs [Koizumi et al, 2007]. RANTES In1.1 C without RANTES À28G had an accelerating effect on HIV disease progression [Wichukchinda et al, 2006].…”
Section: Introductionmentioning
confidence: 98%